Effects of Conditioned Medium of Co-Culture IL-2 Induced NK Cells and Human Whartonâs Jelly Mesenchymal Stem Cells (hWJMSCs) on Apoptotic Gene Expression in a Breast Cancer Cell Line (MCF-7) - Wahyu Widowati; Diana Krisanti Jasaputra; Philips Onggowidjaja; Sutiman Bambang Sumitro; Mochammad Aris Widodo; Ervi Afifah; Dwi Davidson Rihibiha; Rizal Rizal; Annisa Amalia; Hanna Sari Widya Kusuma; Harry Murti; Indra Bachtiar (Journal of Mathematical and Fundamental Sciences, 2019)
Breast cancer (BC) is the most prevalent type of cancer among women and one of the major causes of cancer mortality in women. Metastasis in breast cancer (BC) occurs due to immunosurveillance deficiency, including impairment of natural killer (NK) cell maturation. Conditioned medium (CM) from human Wharton's jelly mesenchymal stem cells (hWJMSC-CM) is known to possess anticancer activity. The CM of co-culture of human recombinant IL-2 treated NK cells and hWJMSCs is expected to boost anticancer activity toward BC cells which can be analyzed from the effect of CM towards secretion of effector molecules and expression of BC cell apoptosis-related genes, and cytotoxic granules in human recombinant IL-2 treated NK (IL-2 NK) and hWJMSCs (IL-2 hWJMSCs). TNF-Î±, IFN-Î³, perforin, granzyme were measured by ELISA, while the inhibition of cell proliferation was measured by MTS assay and BC cell apoptosis by flow cytometry and apoptotic gene expression by RTPCR. CM from co-cultured hWJMSCs and IL-2 NK cells inhibited NK and BC cell proliferation, increased expression of Bax and p53 and decreased the number of Bcl-2 in BC cells. In conclusion, CM of co-culture IL-2 treated NK cells and hWJMSCs induce apoptosis in BC cells as indicated by increased Bax and p53 expression and decreased Bcl-2 expression.